2013
DOI: 10.1109/tbme.2013.2254714
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Intrabody Communications for Body Area Network Applications

Abstract: The rapid increase in healthcare demand has seen novel developments in health monitoring technologies, such as the body area networks (BAN) paradigm. BAN technology envisions a network of continuously operating sensors, which measure critical physical and physiological parameters e.g., mobility, heart rate, and glucose levels. Wireless connectivity in BAN technology is key to its success as it grants portability and flexibility to the user. While radio frequency (RF) wireless technology has been successfully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
194
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(196 citation statements)
references
References 45 publications
2
194
0
Order By: Relevance
“…In the literature, two approaches of HBC are widely discussed [2]. In the first approach, the transmitter uses two electrodes, which are attached to the body, to differentially couple modulated current into the body, resulting in a gradient of electric potential around it.…”
Section: Human Body Communication (Hbc)/intrabody Communication (Ibc)mentioning
confidence: 99%
“…In the literature, two approaches of HBC are widely discussed [2]. In the first approach, the transmitter uses two electrodes, which are attached to the body, to differentially couple modulated current into the body, resulting in a gradient of electric potential around it.…”
Section: Human Body Communication (Hbc)/intrabody Communication (Ibc)mentioning
confidence: 99%
“…Intrabody communication (IBC), also known as human body communication (HBC), is a wireless communication technique in which the human body becomes an integral part of the communication channel, [1,2]. Transmitter and receiver IBC units are placed directly on the skin or in its close proximity, and their maximal distance is the subject's height.…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental investigation, it was found that the large scale body behavior, such walking, sitting, and standing, has little effect on the channel [54,55]. The joint behavior, such as joint flexion or extension, can cause gain variate in 2∼5 dB [56,57], while phase is little affected [57]. The channel characteristics' analysis is shown in Table 3.…”
Section: Channel Characteristics and Transmission Parametersmentioning
confidence: 99%
“…The promising solution to enable the continuous physiological data monitoring is to deploy the body area network (BAN) [6,7], where tiny-size sensors and actuators are utilized to monitor the physiological data and provide the therapeutic functions (i.e., administrate the insulin dosage, control the rates of cardiac pacemaker, etc.) [6,8,9].…”
Section: Introductionmentioning
confidence: 99%